Case reportsMixed connective tissue disease presenting with progressive scleroderma symptoms in a 10-year-old girl - Latuśkiewicz-Potemska, Joanna; Zygmunt, Agnieszka; Biernacka-Zielińska, Małgorzata; Stańczyk, Jerzy; Smolewska, Elżbieta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Mixed connective tissue disease (MCTD) is a systemic inflammatory disease affecting connective tissue with the underlying autoimmunological mechanism. The core of MCTD is an appearance of symptoms of several other inflammatory diseases of connective tissue – systemic lupus erythematosus, systemic scleroderma, poly- or dermatomyositis, rheumatoid arthritis at the same time, accompanied by a high level of anti-ribonucleoprotein antibodies (anti-U1RNP). The disease was described more than 40 years ago by Sharp et al. During recent years, many efforts to better understand clinical and serological features of MCTD have been made. Diagnosis of MCTD can be difficult. Obligatory international diagnostic criteria are required to be fulfilled. Several versions of such criteria have been proposed, but the most widely used one was described by Kasukawa. There is no consensus about treatment – a choice of drugs depends on symptoms. We present a case of a 10-year-old girl with sclerodactyly and trophic damages of fingers accompanied by symptoms of Raynaud’s phenomenon. After an almost 2-year course of the disease, a diagnosis of MCTD has been established.